A Dual‐Gate MoS2 Photodetector Based on Interface Coupling Effect. Issue 1 (26th November 2019) - Liao, Fuyou; Deng, Jianan; Chen, Xinyu; Wang, Yin; Zhang, Xinzhi; Liu, Jian; Zhu, Hao; Chen, Lin; Sun, Qingqing; Hu, Weida; Wang, Jianlu; Zhou, Jing; et al.
Abstract: 2D transition metal dichalcogenides (TMDs) based photodetectors have shown great potential for the next generation optoelectronics. However, most of the reported MoS2 photodetectors function under the photogating effect originated from the charge‐trap mechanism, which is difficult for quantitative control. Such devices generally suffer from a poor compromise between response speed and responsivity ( R ) and large dark current. Here, a dual‐gated (DG) MoS2 phototransistor operating based on the interface coupling effect (ICE) is demonstrated. By simultaneously applying a negative top‐gate voltage ( V TG ) and positive back‐gate voltage ( V BG ) to the MoS2 channel, the photogenerated holes can be effectively trapped in the depleted region under TG. An ultrahigh R of ≈10 5 A W −1 and detectivity ( D *) of ≈10 14 Jones are achieved in several devices with different thickness under P in of 53 µW cm −2 at V TG = −5 V. Moreover, the response time of the DG phototransistor can also be modulated based on the ICE. Based on these systematic measurements of MoS2 DG phototransistors, the results show that the ICE plays an important role in the modulation of photoelectric performances. The results also pave the way for the future optoelectrical application of 2D TMDs materials and prompt for further investigation in the DG structured phototransistors. Abstract : A dual‐gated multilayer MoS2 phototransistor is fabricated to demonstrate an interface coupling effect (ICE) for optoelectronic applications. Various device performance parameters can be modulated based on the ICE. An ultrahigh photoresponsivity of ≈10 5 A W −1 and detectivity of ≈10 14 Jones are achieved.